2012
DOI: 10.1111/j.1754-4505.2012.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral health in patients with multiple sclerosis and epilepsy: A survey in a neurology clinic

Abstract: This study investigated the impact of oral health on neurological disorders using the Oral Health Impact Profile (OHIP). A total of 460 subjects completed the OHIP, including 141 control subjects who did not have any neurological conditions. Of the 319 subjects with a neurological diagnosis who were enrolled in the study, 31% had multiple sclerosis (MS), 34% had epilepsy, and 34% had other neurological conditions. Compared to the control group, mean age (p = .001), education (p = .003), and household income le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…8 There is a lack of quality information on the oral health of people with MS. Current evidence is inconsistent: it often involves smallscale observational findings; is limited by current measurement tools designed for the general population; or is confined to subsets of participants, such as females or high disability groups. [9][10][11][12][13] One such study investigating the oral health status of Australian people with MS was published in 1993 and involved 22 cases. 14 This study found a higher rate of temporomandibular joint (TMJ) dysfunction, but no differences in the number of decayed, missing or filled teeth from the general population.…”
mentioning
confidence: 99%
“…8 There is a lack of quality information on the oral health of people with MS. Current evidence is inconsistent: it often involves smallscale observational findings; is limited by current measurement tools designed for the general population; or is confined to subsets of participants, such as females or high disability groups. [9][10][11][12][13] One such study investigating the oral health status of Australian people with MS was published in 1993 and involved 22 cases. 14 This study found a higher rate of temporomandibular joint (TMJ) dysfunction, but no differences in the number of decayed, missing or filled teeth from the general population.…”
mentioning
confidence: 99%